2D Active Antenna Array Design for FD-MIMO System and Antenna Virtualization Techniques - Ioannis Tzanidis; Yang Li; Gary Xu; Ji-Yun Seol; JianZhong (Charlie) Zhang (International Journal of Antennas and Propagation)
Full dimension MIMO (FD-MIMO) is one of the key technologies presently studied in the 3GPP for the next generation long-term evolution advanced (LTE-A) systems. By incorporating FD-MIMO into LTE/LTE-A systems, it is expected that system throughput will be drastically improved beyond what is possible in conventional LTE systems. This paper presets details on the 2D active antenna array design for FD-MIMO systems supporting 32 antenna elements. The FD-MIMO system allows for dynamic and adaptive precoding to be performed jointly across all antennas thus achieving more directional transmissions in the azimuth and elevation domains simultaneously, to a larger number of users. Finally, we discuss 2D antenna array port virtualization techniques for creating beams with wide coverage, necessary for broadcasting signals to all users within a sector, such as the CRS (Common Reference Signal).